Circular Migrant Workers and Housing in Indian Cities: A View from Ahmedabad - Renu Desai (Vikalpa)
The paper examines the living spaces and related experiences of circular labour migrants in the construction sector in Ahmedabad; and interrogates the urban policy, planning and governance regimes as well as labour legislation and governance regimes shaping these. The paper also pays attention to migrants’ agency in shaping their housing in the city in the context of these regimes and their own multilocal lives. Their housing question is also situated in the context of the broader housing question of the urban poor which consists of a diversity of groups facing shared and differentiated exclusions and vulnerabilities in the city.